Microeconomics - Pindyck, Robert S.; Rubinfeld, Daniel L. (New Jersey : Prentice-Hall, 1998)
Economics
2003-02-24
Keywords: Microeconomics; Supply; Demand; Consumer behavior; Production; investments; Capital market